Retinal overexpression of angiopoietin-2 mimics diabetic retinopathy and enhances vascular damages in hyperglycemia - Pfister, Frederick; Wang, Yumei; Schreiter, Kay; vom Hagen, Franziska; Altvater, Karin; Hoffmann, Sigrid; Deutsch, Urban; Hammes, Hans-Peter; Feng, Yuxi (Acta diabetologica, 2010)
Our previous data suggested that angiopoietin-2 (Ang-2) is linked to pericyte loss, thereby playing an important role in diabetic retinopathy. In this study, we investigated the effect of retinal overexpression of human Ang-2 (mOpsinhAng2 mouse) on vascular morphology in non-diabetic and streptozotozin-induced diabetic animals. Pericyte (PC) coverage and acellular capillary (AC) formation were quantitated in retinal digest preparations after 3 and 6 months of diabetes duration. The degree of retinopathy in non-diabetic mOpsinhAng2 mice at 3 months (−21% PC, +49% AC) was comparable to age-matched diabetic wild type mice. Diabetic mOpsinhAng2 mice exhibited significantly worse vascular pathology than wild type counterparts at 6 months. Quantitative PCR revealed that human Ang-2 mRNA was highly overexpressed in retinas of transgenic mice. Our data demonstrate that overexpression of Ang-2 in the retina enhances vascular pathology, indicating that Ang-2 plays an essential role in diabetic vasoregression via destabilization of pericytes.
Online veröffentlicht: 24. Februar 2009
Gesehen am 02.05.2023